Dissecting modular synthases through inhibition: A complementary chemical and genetic approach - Vickery, Christopher R.; McCulloch, Ian P.; Sonnenschein, Eva C.; Beld, Joris; Noel, Joseph P.; Burkart, Michael D. (Bioorganic & medicinal chemistry letters, 2020)
[Display omitted] Modular synthases, such as fatty acid, polyketide, and non-ribosomal peptide synthases (NRPSs), are sophisticated machineries essential in both primary and secondary metabolism. Various techniques have been developed to understand their genetic background and enzymatic abilities. However, uncovering the actual biosynthetic pathways remains challenging. Herein, we demonstrate a pipeline to study an assembly line synthase by interrogating the enzymatic function of each individual enzymatic domain of BpsA, a NRPS that produces the blue 3,3′-bipyridyl pigment indigoidine. Specific inhibitors for each biosynthetic domain of BpsA were obtained or synthesized, and the enzymatic performance of BpsA upon addition of each inhibitor was monitored by pigment development in vitro and in living bacteria. The results were verified using genetic mutants to inactivate each domain. Finally, the results complemented the currently proposed biosynthetic pathway of BpsA.